Rare Homozygous CTSC Deletion in Siblings with Papillon-Lefevre Syndrome: A Case Report - Fatima AlQaydi; Mohamed Ahmed (BioMed Target Journal)
Papillon-Lefevre syndrome (PLS) is an extremely rare autosomal recessive genodermatosis caused by mutations in the cathepsin C (CTSC) gene. It is characterized by palmoplantar keratoderma (PPK), periodontopathy, intracranial calcifications, and recurrent pyogenic infections. We encountered an Emirati family in which two siblings were diagnosed with PLS. A 7-year-old male was brought to our clinic with dry, scaly plaques on the palms and soles, first noted at the age of one month. Examination revealed well-defined, psoriasiform, erythematous keratotic plaques on the soles, elbows, and knees bilaterally. An infected boil was noted on his right arm. Periodontologists routinely followed the patient due to severe periodontitis, multiple dental caries, and premature loss of deciduous teeth. Radiographic imaging of the skull revealed intracranial calcifications. His developmental history was notable for learning difficulties. His 5-year-old brother also showed PPK and similar dental abnormalities. Both children were born to first-cousin consanguineous parents. Initially misdiagnosed as plaque psoriasis. He was treated with topical corticosteroids and keratolytics (salicylic acid and urea), with no improvement. Methotrexate (0.5 mg/kg/week) was given for three months, resulting only in transient improvement. The condition relapsed shortly after cessation. Oral acitretin (0.5 mg/kg/day) was then initiated, resulting in the complete clearance of hyperkeratosis after five months, with no adverse effects. Genetic analysis revealed a homozygous deletion of exons 3 to 7 in the CTSC gene, a rare variant linked to PLS and reported for the first time in the testing laboratory’s internal database.